2022
DOI: 10.1038/s41467-022-30775-w
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA cluster C19MC confers differentiation potential into trophoblast lineages upon human pluripotent stem cells

Abstract: The first cell fate commitment during mammalian development is the specification of the inner cell mass and trophectoderm. This irreversible cell fate commitment should be epigenetically regulated, but the precise mechanism is largely unknown in humans. Here, we show that naïve human embryonic stem (hES) cells can transdifferentiate into trophoblast stem (hTS) cells, but primed hES cells cannot. Our transcriptome and methylome analyses reveal that a primate-specific miRNA cluster on chromosome 19 (C19MC) is ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 70 publications
4
30
0
Order By: Relevance
“…However, it is currently unknown why this heterozygous mutation did not show a 100% penetrance in our experiments. One explanation could lie in the naïve versus primed stage of the used human embryonic stem cell line: in a recent study, it was revealed that the C19MC is relatively highly expressed in naïve hESCs, whereas its transcriptional activity is declined in primed stem cells [ 53 ]. In our culturing conditions, the HuES9 ESC line rather contains primed cell populations, and the lower expression of the miRNA cluster in those cell types might hinder the detection of the position effect in pri-miRNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is currently unknown why this heterozygous mutation did not show a 100% penetrance in our experiments. One explanation could lie in the naïve versus primed stage of the used human embryonic stem cell line: in a recent study, it was revealed that the C19MC is relatively highly expressed in naïve hESCs, whereas its transcriptional activity is declined in primed stem cells [ 53 ]. In our culturing conditions, the HuES9 ESC line rather contains primed cell populations, and the lower expression of the miRNA cluster in those cell types might hinder the detection of the position effect in pri-miRNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…Naïve hPSCs give rise to a transient pre-implantation TE state when cultured in BMP4, Activin/Nodal inhibitor A83-01, MEK inhibitor PD03, and a Janus Kinase inhibitor. TE cells can then be transitioned to stable post-implantation hTSCs in SAVECY or ACE, a reduced version of SAVECY [29,30] primed, hPSCs display complete activation of placentally imprinted C19MC miRNAs [105], which is one of the original trophoblast criteria proposed by Lee et al [38]. Ectopic activation of C19MC miRNAs in primed hPSCs enhanced their potential to differentiate into proliferative hTSCs with full differentiation potential towards specialized trophoblast lineages [105].…”
Section: Is It Possible To Derive Human Trophoblast Stem Cells From P...mentioning
confidence: 99%
“…However, there may yet be subtle but significant differences between hTSC-like cells derived from naïve and primed states. For example, a recent study from the Arima laboratory reported that hTSCs derived from naïve, but not primed, hPSCs display complete activation of placentally imprinted C19MC miRNAs [ 105 ], which is one of the original trophoblast criteria proposed by Lee et al [ 38 ]. Ectopic activation of C19MC miRNAs in primed hPSCs enhanced their potential to differentiate into proliferative hTSCs with full differentiation potential towards specialized trophoblast lineages [ 105 ].…”
Section: Is It Possible To Derive Human Trophoblast Stem Cells From P...mentioning
confidence: 99%
See 1 more Smart Citation
“…In human embryonic stem (hES) cells, C19MC expression is important for the differentiation of hES into human trophoblast stem cells (hTS). Using CRISPR/Cas gene editing tools, the authors further demonstrate that C19MC is critical in hTS maintenance ( Kobayashi et al, 2022 ). The exact mechanism behind C19MC stem cell maintenance is uncertain but it may involve the C19MC-induced upregulation of pluripotent factors octamer-binding transcription factor 4 ( OCT4 ) and fibroblast growth factor 4 ( FGF4 ) ( Mong et al, 2020 ).…”
Section: Microrna Regulation Of Trophoblast Invasion Spiral Artery Re...mentioning
confidence: 99%